VISUALISASI GEL AKRILAMIDA SIDIK JARI DNA 49 GENOTIPE PADI (Oryza sativa L) MENGGUNAKAN MARKA SSR (Simple Sequence Repeat) - Carolin Sonia Saiallagan; Muhammad Syafi’i; Muhammad Yamin Samaullah; Untung Susanto; Estria Furry Pramudyawardani; Desy Prastika (Jurnal Ilmiah Wahana Pendidikan, 2022)
Micronutrient deficiency remains a major concern in Indonesia, demonstrating how critical it is to meet micronutrient requirements, particularly for Zn micronutrients. Zn can boost a child’s IQ and lessen the risk of bleeding during childbirth (Kennedy et al, 2003). Inpara 1, Inpara 2, Inpara 3, Inpara 4, Inpara 5, Inpara 7, Inpara 9, Aek Sibundong, Bahbutong, Baroma, Batu tei, Ciasem, Cibodas, Cibogo, Cigeulis, Ciherang, Cialamaya Muncul, Cisokan, Conde, Fatmawati, IR 64, and Ketonggo) and 10 SSR markers with high Zn content were used as genetic material (RM475, RM3322, RM441, RM5607, RM335, RM300, RM162, RM3331, RM8007, and RM243). Contamination and the leftover solution used in the DNA extraction and isolation method can generate smears on some rice genotyping samples